2012
DOI: 10.33899/rden.2012.65076
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Er: YAG Laser, Alumi-num oxide and diamond bur on surface treatment of Aged Composite Resin to Repair Restoration

Abstract: Aims: Aim of this study is to investigate the effect of Er: YAG Laser, the sand blasted with aluminum oxide and wearing with diamond bur as a surface treatment to the bond strength of repaired composite resin after aged. Materials and Methods: Sixty Teflon mold (4mm×2mm), of Tetric® Ceram prepared. The specimens were randomly separated into six groups and undergo the following surface treatments: G1 no treatment (control), G2-G4 treated with a different amount of laser energy (40, 60, 80 mJ Er: YAG laser respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Following air abrasion, some of the resin matrix is removed and the surface fillers are exposed resulting in an increased surface roughness of the composite resin. 8 , 23 Several previous studies have reported contradictory findings about air abrasion. In some studies, sandblasting promoted the best repair bond strength, 1 , 25 , 26 while a reduction in repair strength after surface abrasion was found in a few studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Following air abrasion, some of the resin matrix is removed and the surface fillers are exposed resulting in an increased surface roughness of the composite resin. 8 , 23 Several previous studies have reported contradictory findings about air abrasion. In some studies, sandblasting promoted the best repair bond strength, 1 , 25 , 26 while a reduction in repair strength after surface abrasion was found in a few studies.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, sandblasting promoted the best repair bond strength, 1 , 25 , 26 while a reduction in repair strength after surface abrasion was found in a few studies. 8 , 27 , 28 This reduction has been ascribed to the exposure of filler particles, and hence decreased amount of available resin for bonding. 8 , 23 It seems that the application of a silane coupling agent following sandblasting in the present study enhanced the bond to the exposed filler particles and thus, increased the repair bond strength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, Al 2 O 3 increased the bonding strength significantly in the repair process of the RBCs. Most of the previous studies have also found that Al2O3 increases the bond strength significantly (16,(24)(25)(26)(27)(28)(29)(30)(31)(32), but a few studies found that opposite results (33,34). Al2O3 has the ability to form micro retention areas and these areas increase wettability and adhesion to the restoration (35).…”
Section: Discussionmentioning
confidence: 99%